The effect of probiotic supplementation combined with aerobic exercise on the antioxidant capacity of college students - Wu, Tong; Chen, Yingfeng; Zhao, Kai; Liu, Chenzhe; Jiang, Wei (Frontiers in Physiology, 2025)
IntroductionThis study examined the effects of probiotic supplementation alone or combined with aerobic exercise on antioxidant capacity and oxidative stress after high-intensity interval exercise (HIIE) in college students.MethodsThirty male college students were divided into three groups: control (C), probiotic (P), and combined probiotic and exercise (PE). The 6-week intervention involved moderate-intensity cycling three times a week. All participants underwent a single session of HIIE protocol. The tests for maximal oxygen uptake (VO2max), elimination rate of lactic acid (ER), blood oxidative stress markers, and blood rheology were performed.ResultsA decrease in superoxide dismutase (SOD) activity was observed at baseline in the P and PE groups (P < 0.01), while significantly increased glutathione peroxidase (GSH-Px) activity and reduced catalase activity were found in the PE group (P < 0.05). In the P and PE groups, SOD activity (P < 0.01) and total antioxidant capacity (T-AOC) level (P < 0.01) were significantly elevated after HIIE. The T-AOC level significantly increased from 0.47 ± 0.03 umol Trolox/mL to 0.78 ± 0.07 umol Trolox/mL in the P group and from 0.56 ± 0.04 umol Trolox/mL to 0.82 ± 0.05 umol Trolox/mL in the PE group. The 8-OHdG level increased significantly in both the C and P groups (P < 0.05), but remained unchanged in the PE group after the intervention. High shear rate whole blood viscosity was significantly decreased in the P and PE groups (P < 0.05). Additionally, a notable decline in plasma viscosity was observed in the PE group. After the intervention, medium and high shear rate whole blood viscosity levels (P < 0.05) were significantly lower in the PE group than in the C group, and plasma viscosity was dropped by 28.64% (P < 0.05). Following the intervention, a significant elevation in VO2max was only observed in the PE group from 38.14 ± 3.11 to 44.5 ± 2.94 mL/kg/min (P < 0.05), with a subsequent increase in ER detected after HIIE (P < 0.05).DiscussionThese findings indicate that combining probiotics with aerobic exercise enhances antioxidant and aerobic capacity more effectively than probiotics alone.